Comparison Principle for Viscosity Solutions with High Growth at Infinity (Journal of Partial Differential Equations, 1997)
This paper is concerned with the comparison principle for viscosity solutions of the nonlinear elliptic equation F(Du, D²u} + |u|^{s-1}u =f in R^N, where f is uniformly continuous and F satisfies some conditions about p (p > 2}. We got the comparison principle for the viscosity solutions with some high growth at infinity, which relies on the relation between p and s.
Keywords: Comparison principle; viscosity solution; high growth at infinity